The spatial and distributional impacts of the Henry Review recommendations on stamp duty and land tax - Wood, G.; Ong, Rachel; Cigdem, M.; Taylor, E. (Australian Housing and Urban Research Institute, 2012)
This report is the second Final Report of a project that examines the impact on supply and affordability from implementation of the Henry Review recommendations in relation to negative gearing, land tax and stamp duty. This report aims to assess the extent to which the Henry Review recommendations on stamp duty and land tax would affect the costs of purchasing and holding properties across geographical locations, and offers estimates of their capitalisation into land values.